Usulan Perbaikan Proses Bisnis pada Pemesanan Mesin Roll Forming - Bazy, Ahmad; Yuliawati, Evi (Universitas Indraprasta PGRI Jakarta, 2024)
In the manufacturing industry, the business process of selling roll forming machines plays an important role in producing products with high quality and high efficiency. Therefore, this research was conducted to improve the effectiveness of business processes on Vietsteel Brand Roll Forming Machine customer orders at PT Vinatech using the Business Process Improvement (BPI) method and streamlining techniques. The potential problems identified lie in making approval profile designs that are still done manually, which results in errors in machine design and delays in shipping goods. After improvements were made to business processes through upgrading efforts in the streamlining category, there was a significant decrease in resource usage and accelerated the customer order business process at PT Vinatech. Thus, the results of this research can support the improvement of quality and efficiency of business processes in customer orders of Vietsteel Brand Roll Forming Machine at PT Vinatech which has a positive impact on customer satisfaction and company profitability.